Challenges, strategies and consequences from the perspective of German nursing home managers during the first wave of the COVID-19 pandemic - a qualitative interview study - Marco Sander; Richard Dano; Anja Bieber; Anna Dammermann; Steffen Fleischer; Claudia Dinand; Martin Müller; Ralph Möhler; Kristin Schultes; Sascha Köpke; Martin N. Dichter; on behalf of the HEICO-study group (BMC Geriatrics, 2023)
Abstract Background The first wave of the COVID-19 pandemic reached Germany between March and May 2020. In order to contain the spread of the virus and particularly protect vulnerable people, the government imposed a lockdown in March 2020. In addition to infection control measures, such as hygiene and social distancing requirements, a general ban on access to nursing homes for relatives and external service providers was issued. Methods To investigate the challenges and consequences of the enacted infection prevention measures and specific strategies for nursing homes in Germany, a multicentre cross-sectional qualitative interview study with nursing home managers and ward managers was conducted. Recorded audio data were transcribed, analysed using thematic framework analysis and reflected in peer debriefings. Results Seventy-eight interviews with 40 nursing home managers and 38 ward managers from 43 German nursing homes were conducted. At organisational level, the following six themes were identified: Appointing a multi-professional crisis task force, reorganizing the use of building and spatial structures, continuous adaption and implementation of hygiene plans, adapting staff deployment to dynamically changing demands, managing additional communicative demands and relying on and resorting to informal networks. To deal with the pandemic challenges also six themes can be described for the direct care level: Changed routines, taking over non-nursing tasks, increased medical responsibility, increased documentation demands, promoting social participation and increased communication demands. Also various negative consequences were identified (four themes): Psychological stress, negative emotional consequences, permanent feeling of responsibility and increased potential for conflicts. Positive emotional consequences were also reported (two themes): resources for the challenges and positive emotional consequences for home managers and staff. Conclusions The results of the described challenges, strategies and consequences allow recommendations as basis for possible approaches and successful adaptation processes in nursing home care in the future. In particular, there is a need for local networks to act in a coordinated way and a need for quantitative and qualitative support for nurses, such as staff support as well as advanced nursing practice, to cope with the challenges of the pandemic.